(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Development of ravaged areas, taking into account soil conservation agriculture of Namangan adyrs on leveled surface of the ravine area new subtypes of technogenic soils are formed, represented by outcrops and mounds. Naked the area is characterized by dense structure and low filtration capacity. Bulk surface differs in subsidence and potential suffusion hazard, profile friability and significant water permeability.